2002
DOI: 10.1097/00002030-200207050-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Senegalese government's highly active antiretroviral therapy initiative: an 18-month follow-up study

Abstract: This study shows that HAART is feasible and well tolerated in African patients. Clinical and biological results were comparable to those seen in western cohorts, despite differences in the HIV-1 subtype distribution and an advanced disease stage when the treatment was initiated. Contrary to other recent studies in Africa, viral resistance rarely emerged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
116
2
9

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(145 citation statements)
references
References 22 publications
18
116
2
9
Order By: Relevance
“…In their study of adherence in clinical practice in Abidjan [23], Eholie et al have shown that most of the reasons given by patients for not taking ARVs were similar to those reported by other African researchers: lack of money, repeated stock-outs of ARVs, fear of drug side effects and negative influence of traditional healers [44,45]. As for the latter reason, in their experience, these patients discontinued ART at the request of traditional healers.…”
Section: Discussionsupporting
confidence: 56%
“…In their study of adherence in clinical practice in Abidjan [23], Eholie et al have shown that most of the reasons given by patients for not taking ARVs were similar to those reported by other African researchers: lack of money, repeated stock-outs of ARVs, fear of drug side effects and negative influence of traditional healers [44,45]. As for the latter reason, in their experience, these patients discontinued ART at the request of traditional healers.…”
Section: Discussionsupporting
confidence: 56%
“…In Haiti, patients had weight gain and improved functional capacity within one year after the initiation of ART (Koenig, Leandre, and Farmer, 2004). Studies in sub-Saharan Africa have similarly shown rapid improvements in immunological outcomes of patients (Laurent et al, 2002;Coetzee et al, 2004). Rapid improvements in clinical outcomes after the initiation of treatment have also been documented for the sample of patients we study in this paper (Thirumurthy et al, 2008;Wools-Kaloustian et al, 2006).…”
Section: Iiia Treatment Of Hiv/aids With Antiretroviral Therapysupporting
confidence: 57%
“…The Chiradzulu programme diff ers from most HAART programmes described so far in Africa with respect to the scaling-up and simplifi cation procedures used and the number of patients already on treatment. [19][20][21] Currently, very few data from programmes currently involved in scaling-up HAART have been reported. [21][22][23][24] Clinical, immunological, and virological treatment outcomes obtained in our study are comparable with those described in cohorts from developing as well as developed countries, [21][22][23][24][25][26] and indicate that despite scarce medical and monitoring resources, a large cohort of patients with advanced stages of HIV disease could clearly benefi t from fi rst-line antiretroviral treatment.…”
Section: Discussionmentioning
confidence: 99%